The Effect of Simulation Methods on Preparedness Flood Disaster - Syam, Ilham; Yulianita, Marisna Eka; Efendi, Suradi; Dewi, Chitra; Zulhijayanti, Zulhijayanti (Indonesian Journal of Global Health Research, 2023)
Throughout 2022, the National Disaster Management Agency (BNPB) noted 3,531 natural disaster events in Indonesia. The disaster that occurred dominated by floods, namely 1,524 incidents Where amount This equivalent to 43.1% of the total national disaster events. The aim of this research is to determine the effect of simulation methods on flood disaster preparedness at SD Inpres Nipa-Nipa Makassar City. This research uses a " pre-experimental " method with a one group pretest-posttest design. The sampling technique is purposive sampling . sample size was 84 people. This research uses a questionnaire as a data collection instrument. the Wilcoxon test results for video simulations are 0.000 < 0.05 and puzzle simulations are 0.000 < 0.05. This means that there is an influence of video and puzzle simulation methods on flood disaster preparedness at SD Inpres Nipa-Nipa Makassar City. Conclusion study This is there is influence simulation to preparedness disaster flood on Inpres Elementary School students Nipa-Nipa . Recommended to the teacher in school For give education or counseling so that you can increase student knowledge about disaster flood And possible preparedness _ done If happen flood in the future come.